Exploring modified cyclodextrins for enhanced encapsulation and release of ethinyl estradiol: Physicochemical characterization and kinetic modeling - Mehrdad Hadadian; Behnam Mahdavi; Esmail Rezaei-Seresht (Journal of Science: Advanced Materials and Devices, 2025)
Ethinyl estradiol (EE) is a synthetic derivative of steroids that is prescribed for treating sexual diseases. Cyclodextrins (CDs) can enhance the solubility, side effects, and physical characteristics of steroids by the formation of an inclusion complex. This study has aimed to provide a comparison between the encapsulated ethinyl estradiol with carboxymethyl-β-CD (CM-β-CD) and β-CD. For this purpose, different steps of the experiments were monitored using FT-IR, XRD, BET, DLS, and Zeta analyses. The morphology of the prepared inclusion complexes was investigated using FE-SEM imaging that shows nano-sized products with non-spherical structures. The thermal stability of EE and its final compounds were assessed through TGA analysis. In addition, encapsulation efficiency (EE%), phase solubility study, in vitro drug release, and their related kinetic studies were conducted by using the UV–visible spectroscopic method. The obtained data reveals that CM-β-CD/EE has roughly 1.5-fold higher water solubility. Besides, the cumulative release for CM-β-CD/EE was found to be 97%, while it was 46% for β-CD/EE. In contrast, the efficacy of the encapsulation process for β-CD was fairly more impressive than CM-β-CD by 97.5 and 90.62, respectively. Phase solubility kinetic study shows the negative enthalpy by −10.91∗104 J/mol for β-CD/EE and −8.32∗104 for CM-β-CD/EE denoting the favored complexation process and the negative entropy by −2.9∗102 J/mol.K for β-CD/EE and −2.07∗102 J/mol.K for CM-β-CD/EE implying an increase in the order of systems for both complexes. Moreover, the study of the kinetic in vitro drug release exhibits two different mathematical models for products with the same release mechanism, non-Fickian, which is governed by multiple processes.